Analisis Perumusan Strategi Komunikasi Radar Jember Digital - Monalisa Alfitri; Aditya Ali (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this research is to find out the formulation of the Radar Jember Digital media communication strategy in knowing the audience. This study used a descriptive qualitative method. The results of this study are that the strategy used by Radar Jember Digital is to obtain information material through research on issues and phenomena that are currently being discussed, information from the website, but not infrequently the information material is taken directly from the field. Then the information is compiled and adapted to the type of information conveyed, whether the news is of the type of straight news, depth news, interpretive news, or features, for news posts uploaded to Youtube Radar Jember Digital, the writing pattern refers to the 5W + 1H formula, the same as news writing. for the media in general in accordance with journalistic rules. The conclusion of the research is that Radar Jember Digital has an audience where the majority are native Jember residents. So, in this case Radar Jember Digital provides more information or news about Jember residents and the surrounding area. Keywords: Communication Strategy, Media Social, Youtube